ANALYSIS OF THE APPLICATION OF SANITATION STANDARD OPERATING PROCEDURES (SSOP) IN THE PROCESS OF FREEZING YELLOWTAIL FISH FILLET (CAESIO CUNING) IN PT. ARTI BUANA LAUTAN INDONESIA - Mutemainna Karim; Syahrul Syahrul; Awaluddin Awaluddin; Muh. Ayusal Salam (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
PT. Arti Buana Lautan Indonesia is a fishery processing company producing frozen yellowtail fish fillets (Caesio cuning) for export markets. This study aimed to analyze the implementation of Sanitation Standard Operating Procedures (SSOP) in the fish fillet freezing process. A descriptive method with a case study approach was used. Data were collected through observations, interviews, and documentation, then analyzed using a checklist based on the Regulation of the Minister of Marine Affairs and Fisheries of the Republic of Indonesia No. 17/PERMEN-KP/2019. The results showed that SSOP implementation was categorized as very good, with an overall average score of 94.71%. The highest score was found in employee health control (96.53%), while the lowest was in water and ice safety (93.94%). Other assessed aspects included cleanliness of food contact surfaces, prevention of cross-contamination, sanitation facilities, chemical handling, and pest control. Overall, SSOP implementation effectively supported product quality assurance and food safety standards for export products.